The Causal Relationship between Tourist Arrivals and Economic Growth: Evidence from Indonesia - FADILAH, Muhamad Rifki; KUNCORO, Haryo; SEBAYANG, K. Dianta A. (Journal of Environmental Management and Tourism, 2018)
The main motivation behind this research because nowadays tourism becomes one of the major industries in Indonesia. However, literature on the causal relationship between the cyclical components of tourist arrivals and economic growth revealed inconclusive especially in the developing countries as Indonesia. This paper aims at investigating whether foreign tourist arrivals contribute to economic growth evidence from Indonesia over the period 2004 (1) – 2016 (12). Then, this research was applied the vector autoregressive (VAR) model. Afterwards, we exploited Hodrick-Prescott de-trending procedure to obtain cyclical components of tourist arrivals and economic growth. By using the test of Granger-causality, we found that causality running from tourist arrivals to economic growth. Furthermore, the VAR model shows that tourist arrivals were pro-cyclical to economic growth, implied that the increase of tourist arrivals promote the economic growth so that foreign tourist arrivals could be the key to escalate Indonesia’s economic growth in short term.